Ferroptosis: Biochemistry and Biology in Cancers - Shi, Zhiyuan; Zhang, Lei; Zheng, Jianzhong; Sun, Huimin; Shao, Chen (Frontiers in Oncology, 2021)
The challenge of eradicating cancer is that cancer cells possess diverse mechanisms to protect themselves from clinical strategies. Recently, ferroptosis has been shown to exhibit appreciable anti-tumor activity that could be harnessed for cancer therapy in the future. Ferroptosis is an iron-dependent form of regulated cell death that is characterized by the oxidization of polyunsaturated fatty acids (PUFAs) and accumulation of lipid peroxides. Ferroptosis has been closely correlated with numerous biological processes, such as amino acid metabolism, glutathione metabolism, iron metabolism, and lipid metabolism, as well as key regulators including GPX4, FSP1, NRF2, and p53. Although ferroptosis could be involved in killing various cancer cells, multiple aspects of this phenomenon remain unresolved. In this review, we summarize the biochemistry and biology of ferroptosis in diverse cancers and discuss the potential mechanisms of ferroptosis, which might pave the way for guiding cancer therapeutics.